Estimation of Carbon Stocks on Mangrove Forests at Pulau Kampai Using Destructive and Non-Destructive Methods - Anton Syahputra Siregar; Zulkifli Nasution; Rahmawaty Rahmawaty (Tunas Geografi, 2023)
Mangrove forests are essential in maintaining the balance of coastal ecosystems and climate change mitigation. This study aimed to analyze carbon stocks in 2022 in natural mangrove forests at Pulau Kampai, Pangkalan Susu Sub District, Langkat District, North Sumatra Province, with an area of approximately 1,786.25 ha. Estimating carbon stocks in this study uses destructive and non-destructive methods using allometric equations from various aboveground and belowground studies. The sampling plots used a circle plot with a radius of 5.64 m. The sampling plot was determined by purposive sampling based on NDVI criteria (low, moderate, dense, high dense) with a sampling plot distance of 20 m from the edge of the coast or river. The destructive sample tree was taken from the dominant species which grew in the study area, namely Rhizophora apiculata, with a diameter of 7.1 cm with a total biomass yield of 91 kg consisting of aboveground biomass of 67.55 kg (74.23%) and belowground biomass was 23.45 kg (25.77 %). Meanwhile, the average C-organic content produced 56% aboveground and 56% belowground. The estimated carbon stocks using this study's conversion factor was 62.06 tons C/ha with a total carbon stock of 110,849.28 tons C. Meanwhile, the conversion factor using other studies was 48.20 tons C/ha with a complete carbon stock of 86,095.30 tons C.Keywords: Destructive, Non-destructive, Carbon Stocks, C-organic, and NDVIÂ